Goodbye iSlave : A Manifesto for Digital Abolition - Qiu, Jack Linchuan, 1973- (Book collections on Project MUSE., 2016)
"Welcome to a brave new world of profit making, propelled by high technology, guarded by enterprising authority, and carried forward by millions of workers. These millions of bodies gather in gigantic factory complexes to produce coveted commodities--iPhones, iPads, and other gadgets--for consumers worldwide. Yet, at these same factories, working conditions are notoriously oppressive, to the point that a number of employees there have committed suicide. In this study, Jack Linchuan Qiu examines systems of domination, exploitation, and alienation in an era of information technology, global connectivity, and individual consumerism engineered by corporations in collusion with national and regional state authorities. Focusing on notorious Taiwanese manufacturer Foxconn, Qiu conceptually develops the idea of iSlavery and the planetary Apple-Foxconn alliance he calls Appconn. Beginning with historical and legal explorations of slavery, he compares conditions of Foxconn workers to those of 17th century transatlantic slaves. Moving on from labor issues, he turns to fanatic consumption of digital media and argues that compulsive free labor contributions to commodity cycles constitute another form of iSlavery. Qiu relies on interviews, news analysis, and first-hand observation to clarify the circumstances faced by Foxconn workers and examine how a transborder working-class civil society was mobilized. He analyzes how media play a role in shaping public opinion and influencing corporate and state policies, ultimately affecting the fate of workers at the very bottom of the problematic new international division of labor"--